A python script to design site‐directed mutagenesis primers. (27th December 2019) - Bi, Chuyun; Huang, Xiaofang; Tang, Dan; Shi, Yuanyuan; Zhou, Lixiang; Hu, Yunzhuo; Chen, Xuanyang; Qi, Shiqian; Lin, Shiqiang
Abstract: Primer design is essential to conduct whole plasmid site‐directed mutagenesis for protein study. Traditionally, primers of mutagenesis are designed manually that is time‐consuming and fallible. Here, we present a Python script for searching primers by presetting parameters of nucleotide composition and percentage of guanine‐cytosine (GC content). The running results showed that the script is able to search primers with mutations of target residue automatically. This script may facilitate primer design for whole plasmid site‐directed mutagenesis and aid protein mutant construction.